Berdirinya Palang Merah Indonesia Cabang Yogyakarta Tahun 1945 - Muchamad Triyanto; Bambang Eka Saputra; R. R. Sri Setyawati Mulianingsih; Zulkarnain Zulkarnain; Lalu M. Istiqlal (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
This research aims to reveal the background to the establishment of the Yogyakarta Branch of the Indonesian Red Cross (PMI) during the early days of Indonesian independence in Yogyakarta. The method used to obtain data and information is by collecting books, archives, and interviews with former PMI members during the war of independence in Yogyakarta. Data processing for this writing is based on a historical approach. Data obtained from various sources is selected and source critique is carried out and arranged in factual relationships to form an understanding which is then expressed in narrative descriptive writing. The results of the research show that the formation of the PMI Yogyakarta Branch was the result of the struggle after the Central PMI was formed on September 17, 1945, which was followed by the formation of PMI branches in Indonesia, especially in big cities including Yogyakarta. The PMI Yogyakarta Branch formation meeting was held in the building of the former War Victims' Family Relief Agency (BPKKP). PMI Yogyakarta Branch was officially formed on September 29, 1945.